Characteristics of sexual behavior problems in children following assessment and treatment - Erla Guðmundsdóttir 1972- (2017)
Background: Reducing the risk of future recidivism in youths with sexual behavior problem (SBP) is important. Research has shown that both children and adolescents with SBP are a heterogeneous group of individuals and that inappropriate sexual behavior is now more visible among youngsters. Information on SBP youth who receive psychological treatment provided by the Government Agency for Child Protection, is lacking in Iceland and therefore the findings will hopefully support professionals treating youth with SBP. Aims: The primary aim was to investigate characteristics of the children that need treatment for SBP and their abusive behavior. The secondary aim was to investigate if children who were risk assessed and subsequently treated by GACP for their SBP, were prosecuted for sex offence after the age of 15. Method: Pre-existing data regarding 128 individuals (age 6-18) who were assessed and/or received psychological treatment provided from GACP, during the years 2009-2017 were evaluated. Those who had an official police record were identified and categorized. Results: 96.1% of the children were male, 46.1% abused a family member and 51.6% abused in the most severe category. Total of 18.8% of the treated participants were prosecuted for sexual offences after the age of 15 and 81.2% were not prosecuted for sex offence. Keywords: sexual behavior problem, recidivism, juveniles, adolescents, children, young offenders, sexual problematic youth, delinquency, psychological treatment, risk assessment